Enhancement of chondrocyte proliferation, distribution, and functions within polycaprolactone scaffolds by surface treatments. Issue 7 (20th November 2014) - Uppanan, Paweena; Thavornyutikarn, Boonlom; Kosorn, Wasana; Kaewkong, Pakkanun; Janvikul, Wanida
Abstract: Enhancement of porcine chondrocyte growth, distribution and functions within polycaprolactone (PCL) scaffolds was attempted using alkaline hydrolysis and oxygen plasma treatment. The hydrolysis of PCL was performed either before or after scaffold fabrication in the preparations of pre‐hydrolyzed PCL (pre‐HPCL) or post‐HPCL scaffolds, respectively. The PCL, pre‐HPCL, and post‐HPCL scaffolds were subsequently plasma‐treated to yield plasma‐treated PCL, plasma‐treated pre‐HPCL, and plasma‐treated post‐HPCL scaffolds, respectively. All scaffolds were comparatively characterized, in terms of surface morphology, hydrophilicity, and atomic composition using scanning electron microscopy, contact angle measurement and X‐ray photoelectron spectroscopy, respectively. The interactions of chondrocytes with individual scaffolds were assessed, in terms of cartilage‐gene expression and cartilaginous matrix production using reverse transcription polymerase chain reaction analysis and glycosaminoglycans (GAGs) assay, respectively. The cell infiltration and cartilaginous matrix distribution were investigated by histological and immunofluorescence analysis. The results revealed that the plasma treatment exhibited a more prominent effect on the enhancement of surface roughness and hydrophilicity of the scaffolds than the alkaline hydrolysis. The scaffolds subjected to both surface treatments stimulated the cells to secret more GAGs and type II collagen. The sequence of hydrolysis of PCL also evidently played a crucial role in the hydrophilicity of the materials and the cartilage‐gene expression and cartilaginous matrix production of the cultured chondrocytes. The hydrolysis of PCL prior to the fabrication, followed by the oxygen plasma treatment of the resulting fabricated scaffold, yielded plasma‐treated pre‐HPCL scaffold with homogeneous hydrophilic characteristics all over the material. Consequently, the cells could proliferate well, infiltrate most deeply and ultimately produce the highest amounts of the cartilage‐specific substances throughout this scaffold. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 103: 2322–2332, 2015.